Imaging Features of Intrahepatic Biliary Cystadenoma and Cystadenocarcinoma on B-Mode and Contrast-Enhanced Ultrasound - Xu, H.-X.; Lu, M.-D.; Liu, L.-N.; Zhang, Y.-F.; Guo, L.-H.; Liu, C.; Wang, S. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
Purpose: To investigate the imaging features of intrahepatic biliary cystadenoma and cystadenocarcinoma on B-mode and contrast-enhanced ultrasound. Materials and Methods: The B-mode and contrast-enhanced ultrasound features of 6 intrahepatic biliary cystadenomas and 7 intrahepatic biliary cystadenocarcinomas were retrospectively analyzed, and the differences between cystadenomas and cystadenocarcinomas were compared. Results: There were no significant differences between cystadenomas and cystadenocarcinomas in terms of patient gender, age, lesion location, size, and shape (all p > 0.05). On conventional ultrasound, biliary cystadenomas were more likely to be multilocular (6/6 for cystadenoma vs. 2/7 for cystadenocarcinoma) and cystadenocarcinomas more likely presented the features of a mural or septal nodule and a nodule diameter > 1.0 cm (0/6 for cystadenoma vs. 5/7 for cystadenocarcinoma). On contrast-enhanced ultrasound, hyper-enhancement (n = 4) or iso-enhancement (n = 2) was present in the cystic wall, septations or mural nodules of the cystadenomas during the arterial phase and the enhancement washed out to hypo-enhancement (n = 6) during the late phase. Cystadenocarcinomas also showed hyper-enhancement (n = 4) or iso-enhancement (n = 3) in the cystic wall, septations or mural nodules during the arterial phase and iso-enhancement (n = 1) or hypo-enhancement (n = 6) during the late phase. Conclusion: Intrahepatic biliary cystadenomas are more typically multilocular cystic lesions. A mural or septal nodule and a nodule diameter greater than 1.0 cm on conventional ultrasound are suggestive of cystadenocarcinomas. Contrast-enhanced ultrasound is helpful for depicting the vascularity of the lesions but there was no significant difference between cystadenomas and cystadenocarcinomas.
Keywords: abdomen; biliary system; bile ducts; ultrasound